Feeding ecology of the Kalahari springbok Antidorcas marsupialis in the Kgalagadi Transfrontier Park, South Africa - Bothma, Jacobus du P. (University of Pretoria, 2013)
Dissertation (MSc (Botany))--University of Pretoria, 2007.